ACCEPTANCE OF MUSIC STIMULATION THERAPY FOR AUDITORY HALLUCINATION PATIENTS - Arum Pratiwi; Agus Sudaryanto (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2015)
Introduction.The majority of increasing rates of mental illness cases cause by recurrence. Music stimulation therapy on patients with hallucinations is one of the modalities of therapy in nursing care. The purpose of this study was to reduce the recurrence rate of patients experienced with hearing voices.Methods.Patients were asked to listen to music when hallucinations appeared. The nurse was accompanying and observing during therapy. After completion of therapy, patients were interviewed using an open ended question how the response toward the music therapy. Interview data were analyzed using narrative strategies of inquiry. In addition the patients were also measured a number of hallucinations that appeared before therapy. The intervention was applied for one month, and then the patients are repeated its measures by the appearance of hallucinations. The Wilcoxon test was utilized to compare differences between before and after intervention.Result. The themes finding that can be developed were the music therapy shows specific responses and the music therapy disrupts hallucinations. While the quantitative analysis, there were the differences mean between before and after the intervention, but the statistical test showed insignificant value.Discussion. Stimulation therapy of hearing voice panned out and eliminated ongoing hallucinations in patients with a medical diagnosis of undifferentiated schizophrenia, but the response of paranoid schizophrenia patients were unsuccessful.Key words: Nursing modalities therapy, schizophrenia, auditory hallucinations